2014
DOI: 10.4319/lo.2014.59.2.0482
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected resurgence of a large submersed plant bed in Chesapeake Bay: Analysis of time series data

Abstract: An historically large (. 50 km 2 ) submersed plant bed in upper Chesapeake Bay virtually disappeared in 1972, following Tropical Storm Agnes. The bed experienced little regrowth until the early 2000s, when plant abundance rapidly increased. Here, we analyze a suite of recent (1984-2010) and historical (1958-1983) time series datasets to assess alternative explanations for the submersed plant resurgence. Change-point analysis showed that spring nitrogen (N) loading increased from 1945 to 1988 and decreased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 38 publications
2
54
0
Order By: Relevance
“…The sudden growth transitions observed in Fig. 6B are similar to sudden increases in vegetation growth observed in the field (Gurbisz and Kemp 2014). These authors reconstructed a time series of submerged aquatic vegetation in Chesapeake Bay, which experienced no growth for 16 yr followed by a period of rapid growth for 10 yr.…”
Section: Discussionsupporting
confidence: 80%
“…The sudden growth transitions observed in Fig. 6B are similar to sudden increases in vegetation growth observed in the field (Gurbisz and Kemp 2014). These authors reconstructed a time series of submerged aquatic vegetation in Chesapeake Bay, which experienced no growth for 16 yr followed by a period of rapid growth for 10 yr.…”
Section: Discussionsupporting
confidence: 80%
“…Analysis of time‐series data from Chesapeake Bay monitoring has revealed many significant trends for key ecological properties in different regions of the estuary. For example, apart from hypoxia volume and duration discussed above, trends have been detected (1) for phytoplankton biomass and community composition (Harding and Perry ; Harding et al a ), (2) for submersed aquatic vegetation areal cover and density (Orth et al ; Gurbisz and Kemp ), and (3) for all eutrophication‐relevant variables in small tributaries where substantial nutrient reductions have taken place (Boynton et al ). Similar analyses in other large, eutrophic coastal systems (Andersen et al ; Riemann et al ) indicate that a wide‐variety of estuaries have responded positively to nutrient loading reductions.…”
mentioning
confidence: 99%
“…Additionally, upper Chesapeake Bay SAV, which includes the Susquehanna Flats bed, surpassed the goal for that region in the early 2000s, likely due to decreased nutrient loading from the Susquehanna River (Orth et al. , Gurbisz and Kemp , Gurbisz et al. ).…”
Section: How Is the Tmdl Likely To Change These Measures Of Resilience?mentioning
confidence: 99%
“…Remarkably, the Susquehanna Flats SAV recently underwent a rapid (2005)(2006)(2007)(2008)(2009)(2010) and complete recovery and was able to withstand two subsequent extreme weather events (Hurricane Irene and flooding associated with the remnants of Tropical Storm Lee in 2011). Research by Gurbisz and Kemp (2014) suggested that recovery was initiated by gradual long-term reductions in nutrient loading coupled with calm conditions and exceptional water clarity during an extended dry period. Although the decreasing nutrient inputs led to gradual improvement in water quality (Orth et al 2010), the drought provided the extra push necessary to tip the system into a new normal of abundant SAV cover.…”
Section: How Is the Tmdl Likely To Change These Measures Of Resilience?mentioning
confidence: 99%